MATHEMATICAL CONCEPT UNDERSTANDING ABILITY AND SELF-REGULATED LEARNING: THE EFFECT OF QUICK ON THE DRAW STRATEGY - Nanang Supriadi; Sunarto Sunarto; Putri Oktaviana; Fredi Ganda Putra (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
The mathematical concept understanding ability and self-regulated learning in mathematics need to be mastered by students to support them in the learning process and solving various mathematical problems. This research aimed to determine the effect of the Quick on the Draw strategy on students' mathematical concepts understanding and self-regulated learning. The sample of this research consisted of fifty-six students, specifically twenty-nine students in the experimental class and twenty-seven students in the control class. Furthermore, this research employed the quasi-experimental with a factorial research design. The research data that had been collected through tests and questionnaires were tested for their normality and homogeneity. The research hypothesis was tested using the Multivariate Analysis of Variance (MANOVA). Based on the results of research and data analysis, it can be concluded that there was an effect of the Quick on the Draw strategy on students' mathematical concept understanding ability and self-regulated learning.Keywords: Mathematical concept understanding; self-regulated learning; quick on the draw strategy. AbstrakKemampuan pemahaman konsep matematis dan self-regulated learning dalam pembelajaran matematika merupakan suatu kemampuan yang perlu dikuasai oleh setiap peserta didik guna menunjang peserta didik dalam proses belajar dan menyelesaikan berbagai permasalahan matematika. Penelitian ini bertujuan untuk mengetahui pengaruh penerapan strategi pembelajaran Quick on the Draw terhadap kemampuan pemahaman konsep matematis dan self-regulated learning peserta didik. Penelitian ini menggunakan sampel sebanyak 56 siswa (kelas eksperimen n = 29 dan kelas kontrol n = 27) dengan jenis penelitian Quasy Eksperimental Design dengan rancangan penelitian faktorial . Teknik pengumpulan data dalam penelitian ini berupa angket dan tes. Teknik analisis data yang digunakan yaitu uji Normalitas dan uji Homogenitas. Pengujian hipotesis dalam penelitian ini menggunakan Uji Multivariate Analysis of Variance (MANOVA). Berdasarkan hasil penelitian dan perhitungan uji Manova, diperoleh kesimpulan bahwa terdapat pengaruh penerapan strategi pembelajaran Quick on the Draw terhadap kemampuan pemahaman konsep matematis peserta didik. Terdapat pengaruh penerapan strategi pembelajaran Quick on the Draw terhadap self-regulated learning peserta didik. Terdapat pengaruh penerapan strategi pembelajaran Quick on the Draw terhadap kemampuan pemahaman konsep matematis dan self-regulated learning peserta didik.Kata Kunci: Pemahaman konsep matematis; self-regulated learning; strategi quick on the draw.